Analisis Banjir Rancangan di Das Way Tebu Kecamatan Gadingrejo Kabupaten Pringsewu - Amin, Muhammad; Amien, Elhamida Rezkia; Ridwan, Ridwan; Adwijaya, Aditia (Jurnal Agricultural Biosystem Engineering, 2022)
Gadingrejo District is one of the sub-districts that often experience of flooding. Based on the Central Statistics Agency in 2020, Gadingrejo Sub-district is the only sub-district that floods 7 times in one year. One thing that can be done is the construction or repair of channels/rivers to dispose of floods by taking into account the design fof lood discharge. This study aims to determine the intensity and maximum design flood discharge at the 2, 5, 10, 25, and 50 year return periods in the Way Tebu watershed, Gadingrejo District, determine and the channel capacity of the Way Tebu river, and determine whether the capacity of the Way Tebu river in Gadingrejo District can accommodate design flooding at 2, 5, 10, 25, and 50 year return periods. This research method uses the rational method to determine the design flood discharge and the continuity equation to dbydischarge capacity. The results of the analysis show that theof value of the flow coefficient in 2011 was 0.233 while in 2019 it was 0.257. From these results, it is known that there are land function experts with an increase in the flow coefficient of 0.024. Rain intensity and maximum design flood discharge in the Way Tebu watershed in the 2-year return period is 4,403 mm/hour with a discharge of 39,577 m³/s, the 5-year return period is 5,914 mm/hour with a discharge of 53,164 m³/s, and the 10-year return period is 6,489 mm/hour with a discharge of 58,333 m/s, a 25-year return period of 6.918 mm/hour with a discharge of 62,185 m/s, and a 50-year return period of 7,102 mm/hour with a discharge of 63,837 m³/s. These results are in accordance with the literature which states that the design flood discharge is directly proportional to the intensity of the rain, where if the intensity of the rain that occurs is low, the resulting discharge will be small. Vice versa, if the intensity is high, the resulting discharge will be high. The discharge capacity of the Way Tebu canal/river in Gadingrejo District is 43,146 m³/sec. The capacity of the Way Tebu river can only accommodate design flood discharges during the 2-year return period. However, at the 5 to 50 year return period the capacity of the Way Tebu canal/river can no longer accommodate the design flood discharge. To prevent and reduce the flood discharge, it is necessary to hold river normalization and water conservation programs as often as possible, such as river deepening or sediment cleaning/dredging.